2022
DOI: 10.1145/3523056
|View full text |Cite
|
Sign up to set email alerts
|

Model Transformation Testing and Debugging: A Survey

Abstract: Model transformations are the key technique in Model-Driven Engineering (MDE) to manipulate and construct models. As a consequence, the correctness of software systems built with MDE approaches relies mainly on the correctness of model transformations, and thus, detecting and locating bugs in model transformations have been popular research topics in recent years. This surge of work has led to a vast literature on model transformation testing and debugging, which makes it challenging to gain a comprehensive vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 203 publications
(294 reference statements)
0
14
0
Order By: Relevance
“…As mentioned by our interviewees, for debuggers there is a need for model transformation specific techniques. Troya et al (2022) showed that there are numerous advances in this area like those by Wimmer et al (2009), Hibberd et al (2007), and Ege and Tichy (2019) but none of them have led to well rounded debuggers yet. Further effort by researchers active in this area is therefore required.…”
Section: Steps Towards Solving the Tooling Problemmentioning
confidence: 99%
“…As mentioned by our interviewees, for debuggers there is a need for model transformation specific techniques. Troya et al (2022) showed that there are numerous advances in this area like those by Wimmer et al (2009), Hibberd et al (2007), and Ege and Tichy (2019) but none of them have led to well rounded debuggers yet. Further effort by researchers active in this area is therefore required.…”
Section: Steps Towards Solving the Tooling Problemmentioning
confidence: 99%
“…Our work builds on two existing fault localization approaches for model transformations. As categorized in a recent survey on model transformation testing and debugging (Troya et al 2022), these are spectrum-based fault localization (Troya et al 2018) and footprint-based fault localization (Burgueño et al 2015). While the former is a dynamic approach, i.e., the model transformation needs to be executed, the latter is static, meaning that the model transformation is not executed, but the transformation definition is directly analyzed.…”
Section: Fault Localization Approaches For Model Transformationsmentioning
confidence: 99%
“…There are several works which focus on testing and debugging of model transformations. A detailed survey on the topic has been recently published in (Troya et al 2022). With respect to the contribution of this paper, we focus on approaches that propose to locate bugs in model transformations in the following discussion on related work.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The correctness of software built using MDE techniques greatly relies on the correctness of model transformations, so it is of prime importance to test them. The core of model transformation testing is typically divided in three phases [72,85], namely test data generation, test suite assessment and oracle function. The first phase is the main focus of this research.…”
Section: Introductionmentioning
confidence: 99%